Universalismul liberal: o moștenire națională? (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
Margaret Canovan argues that liberal political theory, including its most universalist and anti-communitarian variants, implicitly depends on the existence of a political community capable of sustaining trust, solidarity, and legitimate authority. While liberal theorists often present principles such as justice, the rule of law, and individual rights as universally applicable, these ideals historically emerged within the context of the nation-state, whose shared identity and generalized trust make liberal institutions possible. Examining thinkers such as Hayek, Oakeshott, John Gray, Roger Scruton, and Adam Seligman, Canovan demonstrates that liberalism cannot easily detach itself from the national communities on which it relies. She concludes that contemporary political theory has largely repressed the concept of the nation, even though it remains an indispensable foundation for democracy, social justice, and liberal governance. This abstract is generated with artificial intelligence.